PKCδ-Mediated Nox2 Activation Promotes Fluid-Phase Pinocytosis of Antigens by Immature Dendritic Cells - Singla, Bhupesh; Ghoshal, Pushpankur; Lin, Huiping; Wei, Qingqing; Dong, Zheng; Csányi, Gábor (Frontiers in Immunology, 2018)
Aims: Macropinocytosis is a major endocytic pathway by which dendritic cells (DCs) internalize antigens in the periphery. Despite the importance of DCs in the initiation and control of adaptive immune responses, the signaling mechanisms mediating DC macropinocytosis of antigens remain largely unknown. The goal of the present study was to investigate whether protein kinase C (PKC) is involved in stimulation of DC macropinocytosis and, if so, to identify the specific PKC isoform(s) and downstream signaling mechanisms involved. Methods: Various cellular, molecular and immunological techniques, pharmacological approaches and genetic knockout mice were utilized to investigate the signaling mechanisms mediating DC macropinocytosis. Results: Confocal laser scanning microscopy confirmed that DCs internalize fluorescently-labeled antigens (ovalbumin) using macropinocytosis. Pharmacological blockade of classical and novel PKC isoforms using calphostin C abolished both phorbol ester- and hepatocyte growth factor (HGF)-induced antigen macropinocytosis in DCs. The qRT-PCR experiments identified PKCδ as the dominant PKC isoform in DCs. Genetic studies demonstrated the functional role of PKCδ in DC macropinocytosis of antigens, their subsequent maturation, and secretion of various T-cell stimulatory cytokines, including IL-1α, TNF-α and IFN-β. Additional mechanistic studies identified NADPH oxidase 2 (Nox2) and intracellular superoxide anion as important players in DC macropinocytosis of antigens downstream of PKCδ activation. Conclusions: The findings of the present study demonstrate a novel mechanism by which PKCδ activation via stimulation of Nox2 activity and downstream redox signaling promotes DC macropinocytosis of antigens. PKCδ/Nox2-mediated antigen macropinocytosis stimulates maturation of DCs and secretion of T-cell stimulatory cytokines. These findings may contribute to a better understanding of the regulatory mechanisms in DC macropinocytosis and downstream regulation of T cell-mediated responses.